Penggunaan bahasa arab lisan dan hubungannya dengan strategi pengurusan sumber - Abdul Rahman, Ghazali Yusri; Nik , Mohd Rahimi; Parilah, M.Shah; Wah, Wan Haslina; Sahrir, Muhammad Sabri (Universiti Kebangsaan Malaysia (UKM), 2012)
The Arabic course at Universiti Teknologi MARA (UiTM) Malaysia is an elective offered to first degree students. The objectives of this study are to investigate (1) the level of oral Arabic practice among UiTM students, (2) the correlation between oral Arabic practice and resource management strategies which consist of four sub components, namely, time and environment strategy, effort regulation strategy, help seeking strategy and peer learning strategy, and (3) the differences in the use of resource management strategies among students with different level of oral Arabic practice. This is a mixed method of quantitative and qualitative study using an adapted questionnaire of self regulated learning strategies and interviews with students. The quantitative data were collected from 455 samples using the stratified random sampling technique. The study found that (1) students used moderately oral Arabic, and their practice outside the classroom was lower than inside the classroom, (2) there were significant correlations between oral Arabic practice and the use of peer learning strategy as well as time and study management strategy, and (3) there were significant differences in the use of peer learning strategy among students with different level of oral Arabic practice. This study suggests that the use of peer learning strategy as well as time and study management strategy have to be increased in order to increase the oral Arabic practice among students, such implementing collaborative grouping activities and using peer assistants which are officially selected among students themselves.